Curativo bioativo de biocelulose associado à lectina frutalina da Artocarpus incisa L. - Silva, Thamyres Freire da (2022)
Dressings are an important segment of the medical and pharmaceutical market for wound care worldwide and have evolved from passive matrices that simply cover and protect the wound to those that promote the delivery of bioactives. Cellulose produced by bacterial fermentation, known as biocellulose (BC), is a high purity material that has been used for the production of passive dressings. The BC matrix when associated with a molecule, which acts in the healing process, becomes a bioactive dressing. The BC was oxidized, aiming to modulate its biodegradability and release rate of the bioactive compound, with sodium periodate to produce 2,3 dialdehyde cellulose (BCOXI). Oxidation provides aldehyde groups available to interact with the bioactives. The objective of this work was to create a model for incorporation of frutalin lectin (FTL) from Artocarpus incisa L (bioactive molecule) into BC and BCOXI. Proteins from the genus Artocarpus have shown healing action, such as ArtinM (formerly called Artocarpin or KM+) which has been used in wound care formulations. The performance of FTL-BCOXI dressings and of FTL-BC was evaluated with independent variables: temperature (5, 15, and 25 °C), immobilization time (6, 15, and 24 h), and frutalin concentration (20, 60, and 100 μg/mL). The BCOXI sample obtained higher yield (4.00 μg frutalin/mg dry BCOXI) when compared to BC (0.54 μg frutalin/ mg dry BC). Confocal Fluorescence Microscopy testing was performed in two parts: first confirming the immobilization of FTL by visualization of the FTL-FITC florescent complex on the dressing and second its IgA-binding activity of a ready-made dressing with FTL in contact with IgA-FITC. In cell viability tests FTL was shown to be non-cytotoxic to fibroblast cultures <50 μg/mL after 24 h of contact, showing toxicity after 48 h. FTL released from the dressing also showed a tendency to accelerate wound closure in vitro observed through the fibroblast migration test. About 97% and 80% of the lectin from OXI 6 and CB 6 dressings, respectively, was released into PBS buffer, pH 7.4, in cell and Franz in about 24 h. These are promising results, which show that the dressing has potential for wound treatment.